Análisis de las prácticas de gestión humana para la retención del personal en la empresa MG Consultores S.A.S. (2021)
This work is carried out in the flower company MG CONSULTORES S.A.S located in the municipality of Chía Cundinamarca, la vereda la Fagua, in the area of roses. The main objective of the work is to design a retention program for the workers of the company MG CONSULTORES SAS, for this a current identification of the policies of the company MG CONSULTORES SAS is carried out in the area of human talent that is available to obtain retention of workers and the causes of staff turnover in the company MG CONSULTORES SAS are measured through surveys. These surveys were carried out in the area of roses variety freedom to a representative sample of 98 workers, generated by statistical results and under the Likert-type scale, sent via online by WhatsApp on the Google Forms platform, carrying out a descriptive-correlational study.